2007
DOI: 10.1103/physrevb.75.054406
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic field dependence of dephasing rate due to diluted Kondo impurities

Abstract: We investigate the dephasing rate, 1 / , of weakly disordered electrons due to scattering from diluted dynamical impurities. Our previous result for the weak-localization dephasing rate is generalized from diluted Kondo impurities to arbitrary dynamical defects with typical energy transfer larger than 1 / . For magnetic impurities, we study the influence of magnetic fields on the dephasing of Aharonov-Bohm oscillations and universal conductance fluctuations both analytically and using the numerical renormaliza… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
25
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 37 publications
(100 reference statements)
1
25
2
Order By: Relevance
“…Except for very low temperatures, where a small residual inelastic scattering is observed, 22,23 these calculations are in very good agreement with the experiments that clearly show that magnetic impurities in concentration as small as 1 ppm can induce substantial inelastic scattering. 13,24,25 The source of the small residual inelastic scattering is unclear: It may be due to some mispositioned magnetic impurities with anomalously small Kondo temperature or structural defects created by the ion implantation, but an intrinsic effect cannot be excluded either, although the residual dephasing seems to be proportional to the impurity concentration. Furthermore, we have to emphasize that other experiments on very dirty metals probably cannot be explained in terms of magnetic scattering, and possibly other mechanisms are needed to account for the dephasing observed at very low temperatures in these systems.…”
Section: Introductionmentioning
confidence: 95%
“…Except for very low temperatures, where a small residual inelastic scattering is observed, 22,23 these calculations are in very good agreement with the experiments that clearly show that magnetic impurities in concentration as small as 1 ppm can induce substantial inelastic scattering. 13,24,25 The source of the small residual inelastic scattering is unclear: It may be due to some mispositioned magnetic impurities with anomalously small Kondo temperature or structural defects created by the ion implantation, but an intrinsic effect cannot be excluded either, although the residual dephasing seems to be proportional to the impurity concentration. Furthermore, we have to emphasize that other experiments on very dirty metals probably cannot be explained in terms of magnetic scattering, and possibly other mechanisms are needed to account for the dephasing observed at very low temperatures in these systems.…”
Section: Introductionmentioning
confidence: 95%
“…Previous studies of EDLT-STO systems have shown Kondo effect at n > 6 * 10 13 with T K > 10 K [7,21]. At our lower carrier density, we might expect much lower T K , so our entire experimental temperature range could be T K , a regime in which magnetic impurities are predicted [22,23] and experimentally demonstrated [24,25] to yield constant-in-temperature dephasing.…”
mentioning
confidence: 99%
“…The Kondo problem is of central importance for understanding low-temperature anomalies in low-dimensional disordered metals [1,2,3,4,5,6,7,8,9,10,11,12], such as the saturation of the dephasing rate [13] and the non-Fermi-liquid behavior of certain magnetic alloys [1,14]. For a clean metal, the screening of a spin-1/2 magnetic impurity is governed by a single energy scale, the Kondo temperature T K .…”
mentioning
confidence: 99%